The Effect of Extra Virgin Olive Oil on LOX-1 and COX-2 in High Fat Diet Rats - Ibrahem Omran Lakhder; Lisyani Suromo; Kis Djamiatun (Journal of Biomedicine and Translational Research, 2016)
Background: High fat diet is a diet containing large amounts of fat consistently, the increase dietary fat and cholesterol which have a key role in growing health problems. Extra virgin olive oil associated with prevention of LDL oxidation, beneficial changes in lipid ratios and low risk for CHD.Objective: to determine the anti-inflammatory effect  of extra virgin olive oil extract to  levels of COX-2 and LOX-1 in the blood in rats induced by high fat dietMethods: This research is an experimental study that used randomized posttest only control group design. 30 Wistar rats which were divided into five groups:  group of control (-) which received  normal diet and group of control (+) which received  high fat diet without  EVOO treatment and three high fat diet groups treated by EVOO 1 mL/kg/day, 2 mL/kg/day and 3 mL/kg/day orally for 2 months. The blood was collected from eyes rats and serum separation by centrifuge. COX-2, LOX-1 concentration was measured by the enzyme linked immunosorbent assay (ELISA).Results: The result of this study showed higher COX-2 concentrations in groups treated with EVOO than control group. COX-2 serum levels of negative control where significantly lower than those of rats treated with 2 ml/kg/day (p = 0.047) and 3 ml/kg/day EVOO (p = 0.014). The COX-2 serum levels of group received 1 ml/kg/day were significantly lower than those of rats received 3 ml/kg/day EVOO (p = 0.027). And showed  not significantly deferent among all groups (p = 0.570).Conclusions: The conclusion of this study has showed that extra virgin olive oil extract might have minor anti inflammatory and antioxidant effect in rats.